Optimum renewable oil for biodiesel production as integer programming problem - Sagbansua, Lutfu; Balo, Figen (Sage Publications Inc, 2025)
During the last decades, the apprehension about environmental pollution and consuming of the global fossil resource reserves has raised the requisition to improve an environmental friendly and renewable fuel. Bio-based diesel fuel, which primarily occurs of methyl-esters in fatty acid is one of the finest replaces for fossil-based diesel fuel. Nowadays, plant oils are the primary source of bio-sourced diesel fuel. The fatty acid formation of manufactured bio-based diesel fuel from different plant-based sources and their features are disparate. The aim of the existent research is to choose the optimal plant oil as bio-based diesel through utilizing mathematical modeling technique. Amon plant-based oil kinds, the question of choosing the optimal plant oil is assessed, utilizing many criteria concerned with their features. This study spotlights a new perception into evaluating the optimal plant oil-derived bio-based diesels for the decision-makers like engine manufacturers and development and research engineers to strengthen the green reformation to provide the fuel economy and emission standards.
Keywords: Biomass; renewable energy; sustainability; biodiesel; plant oil; integer programming